What comorbidities accompany sarcoidosis? A large cohort (n=1779) patients analysis - Martusewicz-Boros, Magdalena M; Boros, Piotr W; Wiatr, Elżbieta; Roszkowski-Śliż, Kazimierz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Sarcoidosis is a systemic granulomatous multiorgan disease with the most common manifestation is in the chest, although the granulomas can also involve all other organs causing variety of symptoms mimicking different diseases. Objectives: To evaluate the incidence of comorbidity in a large group of patients with sarcoidosis diagnosed or followed in referral center for lung diseases in Poland. Patients and Methods: We performed a retrospective analysis in a group of 1779 patients discharged with the final diagnosis “sarcoidosis” (ICD-10: D86) from January 2008 to October 2011. Results: The majority (79.2%) were diagnosed as pulmonary and/or lymph node sarcoidosis (D86.0, D86.1, D86.2). Sarcoidosis of other and combined sites (D86.8) were diagnosed in 15.8% and unspecified (D86.9) in 5.0% of patients. At least one comorbid condition was noted in 54% of the patients, most frequently arterial hypertension (22.4%), thyroid disorders (5.6%), diabetes mellitus (5.0%), COPD (4.3%) and obesity (3.3%). Using linear regression models, the associations between the number of comorbidities and age and extent of the disease were found (p<0.001). Patients with multiorgan sarcoidosis were more likely to have a comorbid condition. Conclusions: More than half of patients with sarcoidosis have a comorbid condition, which is more likely in older patients and those with multiorgan involvement. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 115-120)